Implementation Teaching at the Right Level Approach to Football Learning in Junior High School - Aldi Abdul Hamid; Tite Juliantine; Reshandi Nugraha (JUMORA: Jurnal Moderasi Olahraga, 2024)
The disparity in student abilities presents a significant challenge in football education at junior high schools, resulting in unequal outcomes and low mastery of technical, cognitive, and Affective. This study addresses the need for tailored teaching approaches by implementing the Teaching at the Right Level (TaRL) method, which groups students based on skill levels to provide inclusive and effective learning. The research aimed to evaluate TaRL’s effectiveness in enhancing psychomotor, cognitive, and affective abilities and increasing the number of students meeting the cut score. The participants were 34 eighth-grade students from SMP Negeri 19 Bandung. A Classroom Action Research (CAR) design was applied, consisting of two cycles: planning, action, observation, and reflection. The intervention included skill-specific learning tailored to different ability levels. Data collection used skill-based tests (dribbling, passing, shooting, juggling), written cognitive assessments (rules and tactics), and behavioral observations (teamwork, motivation, discipline). Data were analyzed descriptively to measure progress between cycles. Results showed a significant improvement, with the percentage of students meeting KKM increasing from 0% to 88%. The study concludes that TaRL effectively bridges skill gaps, improves learning outcomes, and motivates students. Future research should explore its scalability in other sports and its integration with technology to enhance engagement and accessibility. The study concludes that TaRL effectively bridges skill gaps, improves learning outcomes, and motivates students. Future research should explore its scalability in other sports and its integration with technology to enhance engagement and accessibility